Morpho-anatomical structure and DNA barcode of Sonchus arvensis L. - Dwi Kusuma Wahyuni; SHILFIANA RAHAYU; PUTUT RAKHMAD PURNAMA; TRIONO BAGUS SAPUTRO; SUHARYANTO; NASTITI WIJAYANTI; HERY PURNOBASUKI (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Wahyuni DK, Rahayu S, Purnama PR, Saputro TB, Suharyanto, Wijayanti N, Purnobasuki H. 2019. Morpho-anatomical structure and DNA barcode of Sonchus arvensis L. Biodiversitas 20: 2417-2426. Tempuyung or show thistle (Sonchus arvensis L.) belongs to the Asteraceae. Morpho-anatomy and DNA (Deoxyribonucleic Acid) barcoding of the plant correlates with species identification and metabolite synthesis. This research aims to look at morpho-anatomical structures and analyze the DNA barcode of Sonchus arvensis L (tempuyung). Three samples used for morpho-anatomical analysis are leaves, stems, roots, fruit, and seeds. Anatomical samples are made using the embedding method. DNA barcode uses multiple locus from plastid genome: rbcL and matK. Morpho-anatomical structure of tempuyung showed a similar structure of Sonchus genus. The stem presents in the intercellular space, whereas the roots and leaves present in the vascular tissue and the seeds. Fruits present in each part of the body. Tissues that formed root are epidermis, cortex, endoderm, and stele. Tissues that formed stem are epidermis, cortex, and stele. Tissues that formed leaf are epidermis, cortex, phloem, and xylem. Tissues that formed the fruit and seed are paranormal and sclerenchyma tissues. Sonchus arvensis sequence for rbcL has a similar 100% maximum identity to rbcL gene of S. arvensis, Sonchus asper, and Sonchus oleraceus, whereas Sonchus arvensis matK sequence has a similar 99.31% maximum identity to other S. arvensis matK sequences in BLAST system. These findings provide morpho-anatomical features and DNA barcoding for identification of S. arvensis. from others species in the same genus. Thus also can be considered as pharmaceutical standard.